Sport between business and civil society (20th EASM conference, 18-21 September 2012, 2012)
Oral presentations Youth Olympics Leadership Issues in Sport Organisations Tourism and Leisure Sport Management Global Sporting Events Sport fans Marketing in and through Sport Sport policy The governance in sport(s) Volunteering in sport Participation in sport. Strategies and challenges Operation and management of sports and leisure facilities Sport, media and journalism Other sport management related issues Workshop: The contribution of science to practice in football Workshop: Elite sport organisation and management for world class performance Workshop: Sport policy the significance of government Workshop: London 2012 success and failure of national elite sport policies Workshop: University teaching in sport management Workshop: Governance of international and national sport organizations Workshop: Volunteering in sport Workshop: ESMQ 2013 Special Issue: Value co-creation in sport management